Significados de Saúde e Doença na Percepção de Crianças com HIV / AIDS/ Gleide de Souza da Costa - Costa, Gleide de Souza da (2010)
Relations implied in cases of infantile illness and treatment are, in most of the cases, entirely mediated by adults, usually by the mother, as if the child were not also able to inform doctors about its own condition. However, we can assume that there are existential dimensions of the disease that only the sick child is fully capable to know and to say. In order to orient adequate treatment and obtain better health results for this population, it is important to grasp the meanings attributed by the child to the illness and the beliefs, perceptions and representations created by the child about its health condition. In this sense, this study aims to apprehend the meaning of health and illness in the perception of HIV seropositive children, considering their social context and process of living with HIV. This study is based on qualitative research and was developed in two Non Governmental Organizations (NGO's), located in the city of João Pessoa (PB) and Manaus (AM), being supported by the Theory of the Social Representations. About 13 children, 07 to 10 years old, with positive diagnosis for HIV by vertical transmission, participated of the research. Data were collected through a Socio-Demographic and Clinical Questionnaire (answered by their responsible adults/caretakers) and, with the children, the technique of Drawing-story with Subject was used, requesting them to make two drawings, of a sick person and of a healthful person, and their respective stories. Children were also asked to tell which drawing they prefer and which of them they identify themselves, and a semi-structured interview concerning the meanings of health and illness among children was used, as well. The socio-demographic and clinical data have been dealt with by descriptive statistics and the interviews by Content Analysis. Drawings and stories have been submitted to procedures proposed by Coutinho (2001). Findings: In relation to clinical data, time passed since the confirmation for diagnosis varied between 03 and 08 years (M = 05 years), all the children are symptomatic, 10 of them had already been affected by opportunist illnesses (pneumonia, tuberculosis and malnutrition), 09 had already been hospitalized a number of times (from 1 week to 2 months). According to information given by caretakers, 11 of these children have got knowledge of their diagnosis of AIDS, in 09 cases communicated by a Psychologist. Mother´s (06) or father´s (03) deaths were experienced by 09 children and 10 children live in contact with other seropositive people (mother [02], father [03], both parents [03], both parents + brothers and sisters [02]. Nowadays, their caretakers are parents (02), mother (04, one of them by adoption), father (02), grandmother (03) and aunt (01). The contents of the semistructured interview and the drawing-story with subject, produced similar and complementary data about seropositive children´s perception of health, strongly associated to playing, to being joyful and to good feeding. Illness, instead, appeared associated to physical limitations for playing, symptomatology, exposition to environmental risks, infection by virus, hospitalization, and medication. Final Considerations: The findings of this study draw attention for seropositive children, in order to stimulate the people legally responsible for them, caretakers and health professionals to adopt differentiated attitudes towards children in treatment, helping them to understand what happens to them and to get better quality of life. The study also stresses the lack and need of much more research on children with HIV/AIDS, which propose actions directly related to children and teenagers and, thus, to develop public policies that would correspond to the yearnings of this population.